Pengaruh Variasi Arus Pengelasan 120 A, 130 A, 140 A, dan 150 A terhadap Kekuatan Tarik pada Material ST 37 dengan Metode Pengelasan Metal Inert Gas (MIG ) - Alexander Sebayang; Efrata Tarigan; Liwat Tarigan (Jurnal Pustaka Cendekia Hukum dan Ilmu Sosial, 2024)
Welding is one of the inseparable parts of manufacturing technology. In the welding process, it is necessary to pay attention to the suitability of the welding construction in order to achieve optimal results. For this reason, welding needs to pay attention to several important things including welding efficiency, energy savings, energy savings, and of course low costs. In the need for high-quality welding such as joints on pressure vessels such as heat exchangers, pressure pipes and bridge construction, other steel structures, welding must be well planned. In this study, the welding method used is Metal Inert Gas (MIG), this is very closely related to electric current, toughness, welding defects, and cracks which generally have a fatal effect on the safety of the welded construction. The purpose of this study was to determine the characteristics of the influence of the welding results using Metal Inert Gas (MIG) using variations of 120 A, 130 A, 140 A, and 150 A currents on tensile strength, on St 37 steel plates. The welding results test used was the destructive test method, namely in the form of a tensile test. The parameters observed were the presence or absence of defects in the test piece of the welding results that were tested for tensile strength. If there is a defect in the form of a crack in the weld metal, referring to the BS EN ISO standard, it is determined whether the welding result is accepted or rejected. Test parameters and matters related to testing refer to the ASTM E8 standard. the greater the MIG welding current on ST 37 steel, the greater the ultimate stress value where the highest ultimate stress value (tu) N / mm2 is at a current of 150 A followed by 140 A, 130 A, 120 A. This is because the greater the welding current, the smoother the microstructure of the welding results will be